2021
DOI: 10.3390/rs13204078
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Adaptive Adversarial Patch Attack for Remote Sensing Image Aircraft Detection

Abstract: With the adversarial attack of convolutional neural networks (CNNs), we are able to generate adversarial patches to make an aircraft undetectable by object detectors instead of covering the aircraft with large camouflage nets. However, aircraft in remote sensing images (RSIs) have the problem of large variations in scale, which can easily cause size mismatches between an adversarial patch and an aircraft. A small adversarial patch has no attack effect on large aircraft, and a large adversarial patch will compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…g Lu et al [61] empirically demonstrated Patch-Noobj's transferability in three scenarios: dataset-to-dataset, model-to-model, and joint both. Wang et al [76] also demonstrated the transferability of the invisibility patch across models and datasets.…”
Section: Patch Attackmentioning
confidence: 99%
“…g Lu et al [61] empirically demonstrated Patch-Noobj's transferability in three scenarios: dataset-to-dataset, model-to-model, and joint both. Wang et al [76] also demonstrated the transferability of the invisibility patch across models and datasets.…”
Section: Patch Attackmentioning
confidence: 99%
“…Karmon et al [30] conducted patch perturbations in both images and networks for which the latter was more effective though not physically attainable. While it was more effective, LaVAN lacked robustness across transformations First for classification tasks [37] and object detection [53] First GAN-based [54], physical patch [55], and to fool cameras [56], [57] First for attacking depth estimation [58] and image semantics [59] Data independent adversarial patch [60], and adaptive adversarial patch [61] DiAP [60], Patch-Noobj [61], RAP (IPatch) [59] in 2021 [37] in 2017…”
Section: A Patch Attacks For Classification Tasksmentioning
confidence: 99%
“…On the other hand, it helped eradicate the requirement of manual camouflage nets to cover assets, because bigger assets or larger numbers of them often made it infeasible. Moreover, Lu et al [61] proposed Patch-Noobj to adaptively scale the patch size based on the size of attacked aircraft, showing attack transferability across both models and datasets.…”
Section: B Patch Attacks For Detection Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…1, need only access to the environment imaged by the victim, whereas digital attacks need access to the victim's test images (e.g., in a memory buffer); in this sense, physical attacks have weaker operational requirements and the associated impact is more concerning. For aerial/satellite RGB imagery, physical attacks on a classifier [11], aircraft detectors [14,40] and a car detector [16] have been investigated but only [16] provided real-world physical test results. For aerial/satellite multi/hyperspectral imagery, our work is arguably the first to consider physical adversarial attacks.…”
Section: Adversarial Attacks In Remote Sensingmentioning
confidence: 99%